1990
DOI: 10.1007/bf02072043
|View full text |Cite
|
Sign up to set email alerts
|

The fasting test in paediatrics: Application to the diagnosis of pathological hypo- and hyperketotic states

Abstract: A 24-h fasting test was performed in 48 control children, in 9 hypoketotic patients with inherited defects of fatty acid oxidation and in 2 hyperketotic patients with inherited defects of ketolysis. The control group was then divided into three age groups on the basis of different adaptation to fasting. Concentrations of blood glucose, lactate, free fatty acids (FFA), 3-hydroxybutyrate, acetoacetate and carnitine were measured after 15 h, 20 h and 24 h of fasting. Significant negative correlations were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
3
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(97 citation statements)
references
References 19 publications
7
84
3
3
Order By: Relevance
“…In an effort to estimate the duration of a safe fasting period, a diagnostic fasting test was performed at the age of 4 years. 12 After 24 h of fasting, blood glucose was 3.6 mmol/l (controls 2.8 -3.8 mmol/l), 13 and there was a moderate metabolic acidosis (pH 7.31; base excess À8.9 mEq/l) with an impressive ketonemia and ketonuria. Plasma 3-hydroxybutyrate concentration at the end of the fasting test was 5.8 mmol/l (controls 1.7 -3.2 mmol/l).…”
Section: Clinical Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to estimate the duration of a safe fasting period, a diagnostic fasting test was performed at the age of 4 years. 12 After 24 h of fasting, blood glucose was 3.6 mmol/l (controls 2.8 -3.8 mmol/l), 13 and there was a moderate metabolic acidosis (pH 7.31; base excess À8.9 mEq/l) with an impressive ketonemia and ketonuria. Plasma 3-hydroxybutyrate concentration at the end of the fasting test was 5.8 mmol/l (controls 1.7 -3.2 mmol/l).…”
Section: Clinical Reportsmentioning
confidence: 99%
“…Plasma 3-hydroxybutyrate concentration at the end of the fasting test was 5.8 mmol/l (controls 1.7 -3.2 mmol/l). 13 The psychomotor development and growth were considered to be normal. Patient 3, a male newborn, was born at 34 weeks of gestation with a birth weight of 1950 g and severe asphyxia.…”
Section: Clinical Reportsmentioning
confidence: 99%
“…Five out of twelve patients displayed a biochemical phenotype suggestive of a ketolysis defect (Bonnefont et al 1990). It was recently reported that especially GSD IX is an unappreciated cause of idiopathic ketotic hypoglycemia (Brown et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, supervised clinical fasting studies have played a central diagnostic role as an informative functional in vivo test (Bonnefont et al 1990), but nowadays these studies are considered obsolete. Moreover, fasting studies are relatively time-consuming, expensive, invasive, and potentially dangerous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation